Impact of opioid use on patients undergoing screening colonoscopy according to the quality of bowel preparation. Issue 3 (9th December 2019) - Lamerato, Lois; Wittbrodt, Eric; Kaur, Manpreet; Datto, Catherine; Singla, Sumit
Abstract : Aims: Constipation associated with opioid therapy for chronic pain may negatively impact colonoscopy success. This retrospective, observational study using administrative data and electronic medical records evaluated the impact of opioid use on colonoscopy outcomes. Methods and Results: Procedural codes were used to identify patients who had a screening colonoscopy at two Henry Ford Health System centers (January 2015–December 2016). All patients had completed a standard uniform bowel preparation protocol. Medication orders and filled prescriptions were used to identify patients with a history of opioid use during the 28 days preprocedure (exposed) and a matched random sample of presumptive opioid nonusers (unexposed). Electronic medical records were reviewed for colonoscopy procedure data and outcomes. The exposed and unexposed groups included 964 and 1054 patients, respectively. Inadequate bowel preparation was significantly more common in the exposed versus unexposed group (18.5% vs 12.7%; P < 0.001). In the exposed and unexposed groups, 97.1 and 98.0% of colonoscopy procedures were completed, respectively ( P = nonsignificant). Total procedure time was slightly increased for the exposed versus unexposed group (23.8 vs 22.5 min; P = 0.039). Polyp identification and cancer diagnosis were similar between groups. Prolonged sedation occurred in three patients in the exposed group and none in the unexposed group. Procedural complications were rare, but the incidence was significantly greater in the exposed versus unexposed group (1.3% vs 0.2%; P < 0.01). Conclusions: Opioid exposure was associated with significant reductions in the quality of preprocedure bowel preparation and an increased risk of complications in patients undergoing colonoscopy. Abstract : Constipation associated with opioid therapy for chronic pain may negatively impact colonoscopy success. This retrospective, observational, cohort study using administrative data and electronic medical records showed that opioid exposure was associated with significant reductions in the quality of preprocedure bowel preparation and an increased risk of complications in patients undergoing colonoscopy.